Phycoremediation of cassava wastewater by Desmodesmus armatus and the concomitant accumulation of lipids for biodiesel production. (September 2019) - Okpozu, Otsai Otsima; Ogbonna, Innocent Okonkwo; Ikwebe, Joseph; Ogbonna, James Chukwuma
Abstract: The present study investigated the coupling of phycoremediation of harmful and malodorous cassava wastewater by Desmodesmus armatus with the biosynthesis of fatty acid methyl esters (FAMEs). Cultivation of the microalga on hydrolysed cassava wastewater + Bold's basal medium led to a reduction of total dissolved solids (TDS) by 72% (548.8 mg L −1 ), electrical conductivity (EC) by 73% (998.1 μs cm −1 ), biochemical oxygen demand (BOD) by 76% (136.20 mg L −1 ) and chemical oxygen demand (COD) by 74% (407.73 mg L −1 ) under heterotrophic mode. Mixotrophic growth mode showed a reduction in TDS by 83% (352.8 mg L −1 ), EC by 83% (621.92 s m −1 ), BOD by 87% (73.56 mg L −1 ) and COD by 92% (121.83 mg L −1 ). Biomass productivity of 70.83 mg L −1 d −1 (mixotrophy) was significantly ( p  < 0.05) higher than 52.14 mg L −1 d −1 (heterotrophy). Overall, the FAMEs produced were of C17 – C19 types, and of excellent quality for biodiesel production. Graphical abstract: Unlabelled Image Highlights: Desmodesmus armatus showed excellent growth characteristics on cassava wastewater. The microalga showed significant (p < 0.05) preference for mixotrophy. Nutrient removal efficiency was 92% in the mixotrophic culture. Nutrient removal efficiency was 74% in the heterotrophic culture. Produced FAMEs were of C17 –C19 types, excellent for biodiesel production.